Relationship Between Advanced Maternal Age, Hiesho (Sensitivity to Cold) and Abnormal Delivery in Japan - Nakamura, Sachiyo; Horiuchi, Shigeko (The open nursing journal, 2013)
In Japan, the proportion of women aged 35 and older giving birth has greatly increased in recent years, and maternal age is continuing to increase. Advanced maternal age is a risk factor for abnormal delivery, as is hiesho (sensitivity to cold). This study aimed to assess whether advanced maternal age and hiesho precipitate premature delivery, premature rupture of membranes, weak labor pains, prolonged labor and atonic bleeding. The study design was a descriptive comparative study with a retrospective cohort group design. Subjects in this study were 2,810 Japanese women in hospital after childbirth. The research methods employed were a paper questionnaire and extraction of data from medical records. Comparing the rate of occurrence of abnormal delivery among women aged 35 to 39 according to whether or not they had hiesho, results were premature delivery OR: 3.51 (95% CI: 1.66-7.43), premature rupture of membranes OR: 1.25 (95% CI: 0.90-1.74), weak labor pains OR: 2.94 (95% CI: 1.65-5.24), prolonged labor OR: 2.56 (95% CI: 1.23-5.26), and atonic bleeding, OR: 1.65 (95% CI: 0.14-2.40) when hiesho was present. Among women aged 40 and over, results were premature delivery OR: 5.09 (95% CI: 1.16-22.20), premature rupture of membranes OR: 1.60 (95% CI: 0.73-3.46), weak labor pains OR: 7.02 (95% CI: 1.56-31.55), prolonged labor OR:7.19 (95% CI: 1.49-34.60) and atonic bleeding OR: 2.00 (95% CI: 0.64-6.23). Regardless of maternal age, the presence of hiesho is a risk factor that can precipitate premature delivery, premature rupture of membranes, weak labor pains, prolonged labor and atonic bleeding. Furthermore, hiesho coupled with advanced maternal age increases the incidence of premature delivery, weak labor pains and prolonged labor.